2019
DOI: 10.5187/jast.2019.61.6.313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of production level and source of fat supplement on performance, nutrient digestibility and blood parameters of heat-stressed Holstein cows

Abstract: The interactive effect of dietary fat supplementation and milk yield level on dairy cows performance under heat stress has not been thoroughly investigated. The purpose of this study was to evaluate the effect of production level, the source of fat supplements and their interaction on dairy cows performance under heat stress. In this study, 64 Holstein multiparous cows were divided into 2 groups and received one of two rations having either calcium salts of fatty acids (Ca-FA) or high-palmitic acid (PA) supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The high temperature can increase the cortisol levels and affect the milk production from cows [24,25]. At the same time, it can increase the milk antioxidant levels which can decrease the milk quality in summer seasons from June to August [26].…”
Section: Resultsmentioning
confidence: 99%
“…The high temperature can increase the cortisol levels and affect the milk production from cows [24,25]. At the same time, it can increase the milk antioxidant levels which can decrease the milk quality in summer seasons from June to August [26].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, THI levels exceeding 98 could cause mortality in cows. Heat stress can increase cortisol levels and affect milk production in cows [ 6 , 37 ]. Bohmanova et al [ 19 ] reported that seasonal differences in milk production are caused by periodic environmental changes throughout the year, which directly affect milk production through reduced dry matter intake and indirectly through fluctuations in the quantity and quality of feed.…”
Section: Resultsmentioning
confidence: 99%
“…The practical management systems during acute heat stress conditions uses physical modification of the environment with/without nutritional modification strategies [18][19][20][21]. Of these nutritional strategies comes the chrono-physiological management, which is an emerging bioscience that recently has been incorporated into the practical management systems of livestock reared under heat stress conditions [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%